1997
DOI: 10.1136/gut.41.5.585
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal metaplasia at the squamocolumnar junction in patients attending for diagnostic gastroscopy

Abstract: Background-The incidence of adenocarcinoma of the oesophagus and gastric cardia is increasing rapidly. Barrett's oesophagus is the major risk factor. Intestinal metaplasia at the squamocolumnar junction in the absence of Barrett's oesophagus is common but its relation to adenocarcinoma and gastro-oesophageal reflux disease is unclear. Aims-To study the prevalence and clinical, endoscopic, and histological associations of intestinal metaplasia at the squamocolumnar junction. Methods-Biopsy specimens were taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(55 citation statements)
references
References 20 publications
4
45
0
6
Order By: Relevance
“…Other studies, for example, have shown an association between the incomplete type of IM and clinical/pathologic features of GERD (47), such as white race, male sex, higher patient age, and active esophagitis. Not all studies, however, have detected these clear-cut associations (48,58). The type and pattern of IM at the GEJ may also help to explain the differences in dysplasia and cancer risk in patients with IM in the cardia related to H. pylori versus those with IM in metaplastic columnar epithelium in the distal esophagus related to GERD (see section below on "Natural History").…”
Section: Intestinal Metaplasia Of the Gastroesophageal Junction Regionmentioning
confidence: 99%
“…Other studies, for example, have shown an association between the incomplete type of IM and clinical/pathologic features of GERD (47), such as white race, male sex, higher patient age, and active esophagitis. Not all studies, however, have detected these clear-cut associations (48,58). The type and pattern of IM at the GEJ may also help to explain the differences in dysplasia and cancer risk in patients with IM in the cardia related to H. pylori versus those with IM in metaplastic columnar epithelium in the distal esophagus related to GERD (see section below on "Natural History").…”
Section: Intestinal Metaplasia Of the Gastroesophageal Junction Regionmentioning
confidence: 99%
“…Chronic inflammation and intestinal metaplasia are often detected at the esophagogastric junction without classical Barrett’s esophagus [8, 9, 10, 11, 12]. These histopathologic lesions reportedly associate with GERD [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Cardia intestinal metaplasia is associated with gastric distal intestinal metaplasia and with Helicobacter pylori infection (8,10,18) . Association of esophageal intestinal metaplasia (short segment), with gastric distal intestinal metaplasia was reported in the literature (32,35) . Cytokeratins CK7 and CK20 expression pattern analysis discriminates correctly between intestinal metaplasia in Barrett's esophagus and intestinal metaplasia of the cardia in the majority of cases (19,20,24) .…”
Section: Discussionmentioning
confidence: 92%